Psychometric Properties and Norming of Learning Agility Index: Online Assessment to Measure Fluid Intelligence - Sari, Novita; Firdaus, Wahyu Maulana; Janurasjaf, Aswin (Fakultas Psikologi Universitas Sanata Dharma, 2024)
The Learning Agility Index (LAI) is an online assessment used to assess Fluid Intelligence, the pure intellectual speed and power evaluated by the ability to solve new problems creatively. Using a battery of five sub-tests, LAI can deliver a global trainability quotient (GTQ) indicating how well an individual performs in a training context. This study aims to analyze psychometric properties and norming for LAI. The research data comprised 28,980 subjects from the online test database for employees selection owned by PT Global Talentlytica Indonesia. The research approach used in this study is classical test theory. Psychometric property analysis utilized Cronbach's alpha reliability estimation method and collected validity evidence based on internal structure. The reliability analysis results showed that the five sub-tests had strong reliabilities with Cronbach's alpha values ranging from 0.92 to 0.97. Confirmatory factor analysis confirmed the measurement model of the Learning Agility Index with CFI 0.988, RMSEA 0.022, and SRMR 0.20. The intelligence levels represented by the measurement results were divided into five levels, ranging from “below average” to “far above average.” These findings prove that LAI is a reliable and valid online assessment for measuring fluid intelligence in the context of employees selection or evaluation.